An 'Omics Approach to Unraveling the Paradoxical Effect of Diet on Perfluorooctanesulfonic Acid (PFOS) and Perfluorononanoic Acid (PFNA)-Induced Hepatic Steatosis. (23rd January 2021) - Pfohl, Marisa; Marques, Emily; Auclair, Adam; Barlock, Benjamin; Jamwal, Rohitash; Goedken, Michael; Akhlaghi, Fatemeh; Slitt, Angela L
Abstract: Perfluoroalkyl substances (PFAS) are a family of toxicants universally detected in human serum and known to cause dyslipidemia in animals and humans. Hepatic steatosis, which is defined as lipid deposition in the liver, is known to be a consequence of poor diet. Similarly, PFAS are known to induce hepatic steatosis in animals on a low-fat chow. This study explored diet-PFAS interactions in the liver and their potential to modulate hepatic steatosis. Male C57BL/6J mice were fed with either a low-fat diet (10% kcal from fat, LFD) or a moderately high-fat diet (45% kcal from fat, HFD) with or without perfluorooctanesulfonic acid (3 ppm, PFOS) or perfluorononanoic acid (3 ppm, PFNA) in feed for 12 weeks. Livers were excised for histology and quantification of PFAS and lipids. The PFOS and PFNA coadministration with HFD reduced the hepatic accumulation of lipid and PFAS relative to the LFD treatment groups. Furthermore, transcriptomic analysis revealed that PFAS administration in the presence of an HFD significantly reduces expression of known hepatic PFAS uptake transporters, organic anion transporter proteins. Transcriptomics and proteomics further revealed several pathways related to lipid metabolism, synthesis, transport, and storage that were modulated by PFAS exposure and further impacted by the presence of dietary fat. Both dietary fat content and the chemical functional head group exerted significant influence on hepatic PFAS accumulation and the resulting biochemical signature, suggesting that diet and structure should be considered in the design and interpretation of research on PFAS induced hepatic steatosis.